1998
DOI: 10.1108/09590559810222940
|View full text |Cite
|
Sign up to set email alerts
|

Retail buyers’ perceptions of quick response systems

Abstract: Quick response (QR) systems are being implemented by retail firms at an ever quickening pace throughout the USA. While dramatic changes occur throughout the retail company adopting QR strategies, it is the buyers and buyers' assistants that are more affected by these changes than other executives in the retail firm. Therefore, the purpose of this study was to investigate the perceptions, attitudes and opinions of retail buyers toward QR. Over 200 buyers from leading department and specialty store firms that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…In their review article, Holm-Hansen and Skytte (1998) identified a number of areas omitted from the "traditional" buying behaviour school, including the growth of private brands, the structure of retail organisations, the use of information and information technology, and the changed role of retailing in the channel as a provider of a wider range of services and experiences. Similarly, Varley (2001) argues that the traditional view of retail buying does not reflect the industry move to a consumer responsive or consumer driven approach, typified by the adoption of Electronic Date Interchange (EDI) and Category Management (CM), or Quick Response (QR) initiatives in the clothing sector (Fiorito et al 1998;Giunipero et al 2001). All of these factors widen the scope of the buying activity beyond its traditional functional boundaries.…”
Section: The Structure Of the Retail Buying Process For Private Grocementioning
confidence: 99%
“…In their review article, Holm-Hansen and Skytte (1998) identified a number of areas omitted from the "traditional" buying behaviour school, including the growth of private brands, the structure of retail organisations, the use of information and information technology, and the changed role of retailing in the channel as a provider of a wider range of services and experiences. Similarly, Varley (2001) argues that the traditional view of retail buying does not reflect the industry move to a consumer responsive or consumer driven approach, typified by the adoption of Electronic Date Interchange (EDI) and Category Management (CM), or Quick Response (QR) initiatives in the clothing sector (Fiorito et al 1998;Giunipero et al 2001). All of these factors widen the scope of the buying activity beyond its traditional functional boundaries.…”
Section: The Structure Of the Retail Buying Process For Private Grocementioning
confidence: 99%
“…(Fiorito et al, 1998;Johnsen, 1997;Hunter, 1990). Thus, corporate management mentality should be an integral component, which supports the goals of AR.…”
Section: Development Of Research Model and Hypothesesmentioning
confidence: 94%
“…An integral component of any QR program is automatic replenishment (AR), which is defined as “an exchange relationship in which the vendor replenishes or restocks inventory based upon actual product usage and stock level information provided by the buyer” (Daugherty et al , 1999, p. 63). Given the essential nature of information exchange, the success of any AR program depends, to some degree, on the performance of the retail buyer (Fiorito et al , 1998; Fairhurst and Fiorito, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study, carried out with manufacturers in Scotland, was based on previous research conducted in the USA with apparel buyers (KSA 1997a, Fiorito et al 1998) and in the UK with Downloaded by [Northeastern University] at 17:20 03 November 2014 fashion retail logistics managers and buyers (Birtwistle et al 2003). A structured questionnaire containing 125 questions was created to enable assessment of manufacturer awareness and implementation of (QR) systems and the development of relationships within the supply chain.…”
Section: Methodsmentioning
confidence: 99%